Quadrupel Bilangan Bulat (a,b,c,d) yang Memenuhi a^2+b^2+c^2=d^2 - Qodriyah Qoyyim; Media Rosha (Journal of Mathematics UNP, 2020)
Abstract — An integer if it satisfies the Pythagorean theorem is called a “Triple Pythagoras” where there is already a building formula from Euclides to determine integers  and  that .The next problem is how to construct the formula to determine the integers of quadruple  and  that satisfy  This research is a theoretical research based on literature study. The purpose of this research is to determine the formula of integer’s quadruple  and  that satisfy and to determine the form that has been obtained. The formula by the first way is obtained , , ,  with terms  is an odd integer,  not a prime number,  and  are factor from  which is  The formula by the second way is    with terms    and  are member of sets {5, 13, 17, 25, 29, …} also applies to it multiplies. Thus formula by the first way obtained (4,7,4,9), (4,13,16,21), etc. And formula by the second way obtained (3,4,12,13), (9,12,8,17), etc. Keywords — Integer, Pythagorean Triple, Euclides' Formulas, Integer’s Quadruple.